Key challenges and countermeasures: a review of undergraduate teaching of neurology in outpatient settings - Jiaqian Zhu; Jingyi Huang; Yunhan Cao; Liming Cao (BMC Medical Education)
Abstract In the modern medical education system, teaching of clinical neurology in outpatient settings is crucial for training future neurologists. The neurology outpatient clinic is a pivotal setting for both initial consultations and follow-up visits. It plays a significant role in the prevention, diagnosis, treatment, and ongoing monitoring of neurological disorders, and is a critical platform for clinical education. Under the guidance of experienced physicians during their clinical rotations, medical students enhance their clinical reasoning ability and skills by learning about the diagnosis and treatment of neurological diseases, thereby laying a solid foundation for becoming competent doctors. Despite the advancements in this field, there is a lack of comprehensive reports on the current status and challenges of teaching neurology in outpatient settings. This gap significantly impedes the development of scientific policies to improve teaching standards. We need to clarify the existing issues to develop effective strategies, such as actively embracing advanced educational achievements and experiences, continuously refining teaching models and methods, and enhancing the quality of education, to cultivate more outstanding medical professionals. This article summarizes the current state and issues of teaching clinical neurology in outpatient settings, and analyzes countermeasures to provide a foundation for future practice and study.